ANALISIS EFEKTIVITAS IMPLEMENTASI REKAM MEDIS ELEKTRONIK TERHADAP WAKTU PENYEDIAAN REKAM MEDIS PASIEN RAWAT JALAN DI RUMAH SAKIT TINGKAT II UDAYANA DENPASAR - Komang Cyntia Irene Imayana; I Wayan Widi Karsana; Rai Riska Resty Wasita (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
Medical records for outpatients at Udayana Level II Hospital are still being carried out manually which affects the provision of medical record time. Based on the results of observations made during the provision of outpatient medical records, that is an average of 18 minutes. This is not in accordance with the minimum service standards of the Ministry of Health of the Republic of Indonesia No. 129 of 2008 with a set standard of 10 minutes.The research design was a quasi-experimental one-group pretest-posttest design. The system development analysis method applied is the System Development Life Cycle (SDLC) which consists of 5 stages, namely Analysis, Design, Implementation, Testing, and Maintenance.The results of the study used usability testing on this electronic medical record system and met the usability standard of 88% or can be classified as "very good". The Mann-Whitney test results get a Significance Asym value of 0.000. The significance value of 0.000 <0.05 indicates the influence of the use of electronic medical records on the provision of outpatient medical records at Udayana Level II Hospital in Denpasar with an average time of providing outpatient medical records is 25 seconds.